2017
DOI: 10.1152/jn.00563.2016
|View full text |Cite
|
Sign up to set email alerts
|

Right prefrontal cortex transcranial direct current stimulation enhances multi-day savings in sensorimotor adaptation

Abstract: We have previously reported that visuospatial working memory performance and magnitude of activation in the right dorsolateral prefrontal cortex predict the rate of manual visuomotor adaptation. Sensorimotor savings, or faster adaptation to a previously experienced perturbation, has been recently linked to cognitive processes. We show that facilitating the right prefrontal cortex with anodal transcranial direct current stimulation enhances sensorimotor savings compared with sham stimulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(17 citation statements)
references
References 36 publications
0
15
2
Order By: Relevance
“…Although we found evidence for overlapping neural processes between late adaptation and savings, there are reports in the literature supporting that savings is more associated with early learning cognitive/strategic processes (Haith et al, 2015;Morehead et al, 2015;Seidler, Gluskin, & Greeley, 2017). One potential explanation for these differential findings is that these previous studies were based on behavioral measures of adaptation (Haith et al, 2015;Morehead et al, 2015;Seidler et al, 2017).…”
Section: Fig Urecontrasting
confidence: 66%
“…Although we found evidence for overlapping neural processes between late adaptation and savings, there are reports in the literature supporting that savings is more associated with early learning cognitive/strategic processes (Haith et al, 2015;Morehead et al, 2015;Seidler, Gluskin, & Greeley, 2017). One potential explanation for these differential findings is that these previous studies were based on behavioral measures of adaptation (Haith et al, 2015;Morehead et al, 2015;Seidler et al, 2017).…”
Section: Fig Urecontrasting
confidence: 66%
“…Remarkably, participants who showed more strengthening of the sensorimotor network demonstrated less savings. In another recent study 8 transcranial direct current stimulation (tDCS) was employed to evaluate whether the right and left dorsolateral prefrontal cortex (DLPFC) and left M1 contribute to savings. Participants adapted dart-throwing movements while wearing laterally displacing prism lenses and while receiving anodal tDCS to one of the aforementioned sites.…”
Section: Introductionmentioning
confidence: 99%
“…For example, the right DLPFC has been linked with working memory contributions to early adaptation 1 , 4 and selection of goal-directed actions 25 . Indeed, recent findings suggest a role for the right DLPFC in savings 8 . Furthermore, previous studies have shown the anterior cingulate cortex (ACC) is recruited during early adaptation 21 and plays a role in assigning value to actions on the basis of relevant feedback 26 .…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is the application of non-791 invasive brain stimulation, which is a technique that appears to be suited to restore some of the age-792 related deficits (Hardwick and Celnik, 2014;Orban de Xivry and Shadmehr, 2014;Grimaldi et al, 2016). 793 A two-fold approach is possible to restore the decline of explicit strategy in elderly: Either directly, by 794 stimulation of a region such as dorsolateral prefrontal cortex that might temporary boost some 795 working memory resources (Seidler et al, 2017), or indirectly, by stimulation of the cerebellum that 796 might boost, the already intact, implicit component of motor adaptation. Finally, we expect that the 797 observed age-related decline of explicit strategy is having widespread consequences on other features 798 and components of motor adaptation such as reduced generalization, increased interference of motor 799 memories, reduced savings and reduced reinforcement learning.…”
Section: Discussionmentioning
confidence: 99%